Long-term high-fat diet disrupts lipid metabolism and causes inflammation in adult male rats: possible intervention of endoplasmic reticulum stress. (2nd January 2023) - Binayi, Fateme; Moslemi, Mehdi; Khodagholi, Fariba; Hedayati, Mehdi; Zardooz, Homeira
Abstract: This study investigated the effect of long-term high-fat diet (HFD) on plasma lipid profile and probability of inflammation in adult rats. After weaning, male offspring were divided into six groups based on diet type and medication. After 20 weeks of dietary intake, 4-PBA (endoplasmic reticulum (ER) stress inhibitor) was injected for three days. Then, blood samples were taken to measure plasma concentrations of low-density lipoprotein (LDL), triglyceride (TG), high-density lipoprotein (HDL), cholesterol, leptin and interleukin 1-β (IL 1-β). The HFD increased body weight and food intake and intra-abdominal fat and thymus weights, which were associated with elevated plasma leptin level. Moreover, HFD increased plasma concentrations of TG, LDL, cholesterol and IL 1-β and decreased HDL level. Injection of 4-PBA reversed the plasma parameters changes caused by HFD. It seems that long-term HFD feeding through inducing the ER stress, disrupted the lipid metabolism and resulted in inflammation.